2022
DOI: 10.1039/d2ra03307k
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxy pendant isatins as potent α-glucosidase inhibitors: reciprocal carbonyl⋯carbonyl interactions, antiparallel π⋯π stacking driven solid state self-assembly and biological evaluation

Abstract: Carbonyl–carbonyl (CO⋯CO) interactions are recently explored noncovalent interactions of significant interest owing to their role in the stability of biomacromolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 77 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…Several therapeutic approaches of diabetes are available, but α-glucosidase inhibitors (AGIs), has been considered a precise and specific strategy for the management of type II diabetes mellitus. AGIs, have been considered a valuable approach because these AGIs slow down the catalytic activity of carbohydrates digestive enzyme α -glucosidase 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Several therapeutic approaches of diabetes are available, but α-glucosidase inhibitors (AGIs), has been considered a precise and specific strategy for the management of type II diabetes mellitus. AGIs, have been considered a valuable approach because these AGIs slow down the catalytic activity of carbohydrates digestive enzyme α -glucosidase 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other hypoglycemic agents that regulate certain biochemical processes, these inhibitors act locally in the human intestine . However, the clinical uses of these are associated with side effects such as abdominal discomfort, diarrhea, and flatulence. Therefore, synthesis of new α-glucosidase inhibitors with no or minimal side effects is still a reasonable need.…”
Section: Introductionmentioning
confidence: 99%
“… 27 However, the clinical uses of these are associated with side effects such as abdominal discomfort, diarrhea, and flatulence. 28 30 Therefore, synthesis of new α-glucosidase inhibitors with no or minimal side effects is still a reasonable need.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that aryl-substituted phenoxy-acetamide scaffolds were reported as potent α-glucosidase inhibitors. C=O moiety of acetamide as the key skeletons anchoring can stabilize α-helices, β-sheets, and other secondary structures of biological macromolecules through participation in various forms of interaction including hydrogen bonding, nucleophile–carbonyl, carbonyl–carbonyl (CO/CO) interaction [ 22 ]. Assessments on diphenylimidazole core attached to the various N-aryl acetamides (Fig.…”
Section: Introductionmentioning
confidence: 99%